Assessing the priority of human rights and mental health: the PHRAME approach. Issue 2 (27th March 2023) - Gronholm, Petra C.; Gill, Neeraj; Carter, Grace; Watson, Danielle; Helmchen, Hanfried; Thornicroft, Graham; Sartorius, Norman
Abstract : Background: Protecting all human rights of people with mental health conditions is globally important. However, to facilitate practical implementation of rights, it is often necessary to decide which of these rights should be given priority, especially when they conflict with each other. Aims: The aim of the Priorities of Human Rights and Mental Health (PHRAME) project is to develop a replicable approach to establish a proposed set of high-priority human rights of people with mental health conditions, to facilitate practical decision-making and implementation of such rights. Method: A two-stage Delphi-style study with stakeholders was conducted to generate a list of key rights of people with mental health conditions, and rank priorities among these rights in terms of feasibility, urgency and overall importance. Results: The stakeholders in this study consistently ranked three rights as top priorities: (a) the right to freedom from torture, cruel inhuman treatment and punishment; (b) the right to health and access to services/treatment; and (c) the right to protection and safety in emergency situations. Conclusions: Insights from PHRAME can support decision-making about the priority to be given to human rights, to guide practical action. This approach can also be used to assess how human rights are prioritised in different settings and by different stakeholders. This study identifies the clear need for a central voice for people with lived experience in research and implementation of decisions about the priority of human rights, ensuring that action respects the opinion of people whose rights are directly affected.